2018
DOI: 10.1007/s11154-018-9461-4
|View full text |Cite
|
Sign up to set email alerts
|

Agreement between medical records and self-reports: Implications for transgender health research

Abstract: A key priority of transgender health research is the evaluation of long-term effects of gender affirmation treatment. Thus, accurate assessment of treatment receipt is critical. The data for this analysis came from an electronic medical records (EMR) based cohort of transgender individuals. A subset of cohort members were also asked to complete a self-administered survey. Information from the EMR was compared with survey responses to assess the extent of agreement regarding transmasculine (TM)/transfeminine (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 17 publications
0
20
0
Order By: Relevance
“…Each transgender cohort member was categorized as TF or TM, based on sex documented at birth. The TM and TF assignment methodology was described and validated previously [ 23 , 24 ]. The receipt of gender-affirming HT was ascertained based on filled prescription information documented in the pharmacy records.…”
Section: Methodsmentioning
confidence: 99%
“…Each transgender cohort member was categorized as TF or TM, based on sex documented at birth. The TM and TF assignment methodology was described and validated previously [ 23 , 24 ]. The receipt of gender-affirming HT was ascertained based on filled prescription information documented in the pharmacy records.…”
Section: Methodsmentioning
confidence: 99%
“…There is limited literature on EHR-based studies with the ability to validate an administrative transgender measure using a ‘gold standard’ comparison measure. 16 The two previous studies that have developed and validated algorithms to identify transgender individuals have both been conducted in non-representative samples in the USA, one using Medicare data 38 and one in a university medical centre. 16 Similar to the current study, the Medicare study found high specificity when comparing an EHR-based and a two-step survey-based transgender measure.…”
Section: Discussionmentioning
confidence: 99%
“… 39 As ‘gold standard’ two-step sex assigned at birth and current gender identity measures of transgender status 12 are slowly being implemented in routinely collected healthcare data sources, in the meantime NLPs to extract free-text data can be used to produce better gold standards against which to measure algorithm performance, as demonstrated by the Medicare study. 38 …”
Section: Discussionmentioning
confidence: 99%
“…Large prospective studies are challenging to conduct in this population. However, novel techniques have been developed to obtain information from existing electronic medical records as described in this issue by Gerth et al 14 .…”
mentioning
confidence: 99%